Using the idea of market-expected return rates on invested capital in the verification of conformity of market evaluation of stock-listed companies with their intrinsic value - Mielcarz, Paweł; Roman, Emilia (Business, Management and Economics Engineering, 2012)
This article presents the concept of investor-expected rates of return on capital of listed companies and the use of these rates in the assessment of the extent to which the stock evaluation of a given entity is compatible with its intrinsic value. The article also features results of the research aimed at verification – with the use of the presented tool – of whether the market value of WSE-listed companies reflects their fundamental value. The calculations presented in the empirical part of the article show that at the beginning of 2011, market evaluation of the most of the analysed entities greatly exceeded their fundamental value.